Trend of research output of journals related to Humanities and Social Sciences - Navaneethakrishnan, S. (Digital Information Research Foundation, 2015)
The Bibliometric research analysis is an inspiring journey with the mind and the story of conclusions has just begun to react with implications when the findings explored through an analysis. The present study could enable to bridge the research gap of bibliometric research on the Humanities and Social sciences discipline in Sri Lanka. This study uses adequate methods to indicate research output by analyzing growth trend of research output of journals related to Humanities and Social Sciences published by Sri Lankan Universities. Further it would generally encourage more research in the field of Humanities and Social Sciences in Sri Lanka.
Keywords: Bibliometrics; Humanities; Social Sciences; Higher education